Examining Legal Recourse and Rehabilitation for Burnt Survivors of Domestic Violence: A Study of Section 337-L (1) in Pakistan - BUZDAR, ZULFIQAR ALI; HAIDER, SYED NAVEED; SHABBIR, SHEEBA; ASHRAF, ROMAN; ZAMAN, FAKHARUZ; MASOOD, RIFFAT (Pakistan Journal of Medical & Health Sciences, 2025)
Background: The section 337-L (1) of the Pakistan Penal Code serves as a pivotal legal instrument, providing a framework for addressing injuries for disturbing normal pursuits of life for about 20 days or more. In this context burns inflicted within the realm of domestic violence surfaces as the most notorious mode of injury to be evaluated in light of this particular section of law. Aim: To identify the correlation between physiological outcomes and the length of hospital stay of survivors of unfortunate victims of burns. Methodology: Data were collected from Accident and Emergency Department of May Hospital Lahore from December 2023 to December 2024. Physiological outcomes were assessed including scar, movement limitation, disfigurement, loss of feeling of sensation and permanent pain or discomfort; participants were categorized based on gender and age group. Statistical analysis was carried out to find the relation between the return to normal physiology when compared with the one of longer hospital stay. Results: The results showed strong correlations between burns and some physiological outcomes, such as scarring, motion impairment and permanent pain or discomfort in survivors. Physiological outcomes were correlated with the severity of prolonged hospitalization, reflecting the limitations of survivors in receiving timely and comprehensive healthcare services. The p value 0.009 found the association defined to be statistically grossly significant. Conclusion: present study demonstrated the urgency to tackle burns through holistic and survivor centered approaches of early detection, trauma informed care, and integrated support services. When healthcare systems prioritize the well-being of survivors and encourage interdisciplinary collaboration, they can contribute to mitigating the ravages of burns and help survivors heal and recover.